IMPLEMENTASI PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2015 TENTANG ITSBAT NIKAH TERPADU PERSPEKTIF MASLAHAH MURSALAH (Studi Pada Pengadilan Agama Kelas IIA. Manna) - Fajri, Aswadi (UIN Fatmawati Sukarno Bengkulu, 2018)
This study discusses the implementation of the determination of Integrated Marriage of Religious Court Class IIA Manna in District Kedurang South Bengkulu Regency. the establishment of marriage is a provision of marriage proven by a religious court. The legal basis of marriage isbat is the Compilation of Islamic Law contained in Article 7 paragraph (1) Com- pilation of Islamic Law affirms that marriage can only be proved by the Marriage Certificate made by the Officer of Marriage Recorders. This indicates that marriages that do not have proof of registration can be submitted to the establishment of mar- riage in religious courts accompanied by certain requirements. The purpose of the isbat marriage is to get a new marriage book through the establishment of ratification in accordance with the Law No. 1 of 1974 without doing aqad marriage again. Among the reasons for implementing the establishment of Integrated Marriage is to provide solutions for couples whose marriages are not recorded. The purpose of this study is to know the rule of law issued by the Supreme Court relating to the establishment of Integrated Marriage and the application of Supreme Court Regulation No. 1 Year 2015 By Manna Religious Court. This type of research is a type of field research using qualitative descriptive approach. The research data is taken directly from the research location and the data is obtained by using interview method, observation and documentation method. After the data collected to analyze the data collected in this study used analytical descriptive-analytic technique, which describes all the things that focus in this research. The results of this study indicate that the Regulation of the determination of Integrated Marriage contained in Perma No 1 Year 2015 which regulates the mechanism of implementation of an integrated determination session. As for the rule of law remains based on existing rules. Meanwhile, the establishment of integrated marriage is conducted by Manna Religious Court in Kedurang sub-district in accordance with Perma No 1 year 2015. Legal basis of the determination of Marriage Regula- tion Terhadi namely KHI Article 7 paragraph (1). While the judge’s consideration in deciding the determination of Integrated Marriage is a problem. With the establishment of marriage, the protection of the rights of each partner because of their marriage has obtained legal recognition and provide assurance of life, property and descent which is the principle that must be kept in Islam (Ushulul Khomsah